Emission trading beyond Europe: linking schemes in a post-Kyoto world - Niels Anger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This paper assesses the economic impacts of linking the EU Emission Trading Scheme (ETS) to emerging schemes beyond Europe, in the presence of a post-Kyoto agreement in 2020. Simulations with a numerical multi-country model of the world carbon market show that linking the European ETS induces only marginal economic benefits: As trading is restricted to energy-intensive industries that are assigned generous initial emissions, the major compliance burden is carried by non-trading industries excluded from the linked ETS. In the presence of parallel government trading under a post-Kyoto Protocol, excluded sectors can however be substantially compensated by international trading at the country level, thus increasing the political attractiveness of the linking process. From an efficiency perspective, a desirable future climate policy regime represents a joint trading system that enables international emission trading between ETS companies and governments. While the Clean Development Mechanism (CDM) cannot alleviate the inefficiencies of linked ETS, in a parallel or joint trading regime the access to abatement options of developing countries induces large additional cost savings. Restricting CDM access via a supplementarity criterion does not significantly decrease the economic benefits from project-based emission crediting.
Keywords: H22; H21; Q58; D61; 330; EU ETS; Emission Trading; Kyoto Protocol; Clean Development Mechanism